HUBUNGAN POWER OTOT LENGAN DAN BAHU DENGAN HASIL LEMPAR LEMBING PADA SISWA KELAS XI SMK KANSAI PEKANBARU - Simbara, Afif; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study was to get the relationship of arm andshoulder muscle power with javelin throwing result at the student of class XI SMK Kansai Pekanbaru. This studyuses quantitative analysis descriptive correlational approach. The population inthis study were as many as 20 samples. While the sample technique used is total sampling (saturated sample). Where all the population as the sample. After that, the data is processed with statistics. Normality test with lillefors testand correlation at significant level a (0,05). The analysis in the calculation between X and Y where Rtabel at significant level a (0,05) = (0,456). Then obtained for Rcount (0,863) > Rtabel (0,456), which means the hypotesis is accepted and the correlation between the arm and shoulder muscle power with javelin throwing result at the student of class XI SMK Kansai Pekanbaru. Then, it can be concluded that the X and Y relationship is significantKey Words: Relationship Of Arm And Shoulder And Javelin Throwing Result